FeS2 / rGO composite material as well as preparation method and application thereof

Through the establishment of an internal electron circulation system in the catalyst and the use of rGO's high specific surface area and conductivity, the problem of difficult regeneration of the iron-based catalyst Fe(II) is solved, and efficient deep degradation of VOCs exhaust gas is achieved. The degradation products are CO2 and H2O, avoiding secondary pollution.

CN119793488APending Publication Date: 2025-04-11SUN YAT SEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411914861.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When existing iron-based catalysts use activation catalytic technology of sulfate radicals to treat VOCs, Fe(II) regeneration is difficult and it is difficult to generate sufficient strong oxidative free radicals, resulting in low degradation efficiency of target pollutants.

Method used

Using FeS2/rGO composite material, an internal electron circulation system is established in the catalyst through S element, providing electrons for the reduction process of Fe(III) to Fe(II), realizing the regeneration of catalytic sites, and using rGO's high specific surface area and conductive properties to improve the adsorption and catalytic oxidation capabilities of the catalyst.

Benefits of technology

The regeneration of Fe(II) can be achieved without excessive oxidizing agent, generating sufficient strong oxidative free radicals, and improving the efficient deep degradation efficiency of VOCs exhaust gas. During the degradation process, VOCs are decomposed into CO2 and H2O, avoiding the generation of secondary gaseous pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793488A_ABST
    Figure CN119793488A_ABST
Patent Text Reader

Abstract

The invention discloses a FeS2 / rGO composite material as well as a preparation method and application thereof, and belongs to the technical field of catalysts. The FeS2 / rGO composite material comprises an rGO carrier and FeS2 particles, the FeS2 particles are dispersed on the surface and in wrinkles of the rGO carrier, and the particle size of the FeS2 particles is 1-5 [mu] m. The FeS2 / rGO composite material provided by the invention can be used for treating VOCs (Volatile Organic Compounds) waste gas by utilizing an activated catalysis (SAOPs) technology of sulfate free radicals in a liquid-phase advanced oxidation technology, and after the composite material is in contact with persulfate, free radicals with super-strong oxidizing capacity, such as SO4.-and. OH, can be efficiently and quickly generated, so that efficient deep degradation of the VOCs waste gas is realized, and the VOCs waste gas can be recycled. In the degradation process, the VOCs can be decomposed into CO2 and H2O.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst technology, and more specifically, to a FeS2 / rGO composite material and a preparation method and application thereof. Background Art

[0002] In recent years, a series of air pollution problems caused by the large-scale emission of volatile organic compounds (VOCs), such as ozone, haze and photochemical smog, have caused frequent respiratory diseases and deterioration of the ecological environment, which has seriously threatened human health and economic development.

[0003] VOCs have many sources and complex characteristics. Existing treatment technologies such as adsorption, absorption, plasma, photocatalysis and thermal storage combustion are difficult to deeply treat them. In addition, due to the high reactivity of VOCs, more toxic secondary gaseous pollutants are easily produced during the treatment process of traditional technologies.

[0004] Liquid phase advanced oxidation technology (AOPs) can produce SO4 efficiently and quickly under normal temperature and pressure conditions. ·- and · OH and other free radicals with super oxidizing ability, thereby achieving efficient and deep degradation of VOCs waste gas. During the degradation process, VOCs can be decomposed into CO2 and H2O without any secondary gaseous pollutants, which has attracted widespread attention in the field of VOCs control.

[0005] Advanced oxidation technology can be divided into thermal catalysis, photocatalysis, electrocatalysis and sulfate radical activation catalysis (SAOPs) according to different oxidation pathways. Among the various AOPs methods, sulfate radical activation catalysis (SAOPs) uses transition metals as catalysts to activate persulfate to produce free radicals, which is the simplest, most efficient, and environmentally friendly because it does not require the addition of additional heat and light sources.

[0006] Prior art CN113198517B discloses a highly dispersed cobalt-iron bimetallic catalyst, which can be used in the treatment of continuous flow VOCs waste gas by SAOPs combined with liquid phase absorption. Prior art CN17920275A discloses an activated carbon-supported micro-nano cobalt disulfide catalyst, which can catalytically degrade benzene-based VOCs in a wet AOP scrubber. It can be seen that the above-mentioned existing catalysts are all cobalt-based transition metal catalysts. However, the cost of the cobalt source is high, and the toxicity is high, which is not environmentally friendly.

[0007] Iron-based catalysts are low-cost, have high catalytic activity and are environmentally friendly. However, the difficulty in regenerating Fe(II) is a major problem that limits the development of iron-based catalysts, which will lead to the rapid deactivation of iron-based catalysts. Therefore, a large amount or even an excessive amount of oxidant is usually required to reduce Fe(III) to achieve the regeneration of Fe(II) and generate enough strong oxidizing free radicals to ensure the effective degradation of the target pollutants, but this will cause ineffective consumption of the oxidant.

[0008] Therefore, the difficulty in regenerating iron-based catalysts Fe(II) is a technical problem that needs to be solved in the current treatment of VOCs waste gas using sulfate radical activation catalytic technology. Summary of the invention

[0009] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of existing iron-based catalysts in treating VOCs using sulfate radical activation catalytic technology, such as difficulty in regenerating Fe(II) and difficulty in generating sufficient strong oxidizing free radicals to achieve effective degradation of target pollutants. A FeS2 / rGO composite material is provided, which has FeS2 particles, and an internal electron circulation system is established in the catalyst by adding the S element to provide electrons for the reduction process from Fe(III) to Fe(II), thereby achieving regeneration of catalytic sites. At the same time, reduced graphene oxide (rGO) with a high specific surface area and excellent conductive properties is used as a carrier to achieve adsorption and catalytic oxidation of VOCs.

[0010] Another object of the present invention is to provide a method for preparing a FeS2 / rGO composite material.

[0011] Another object of the present invention is to provide an application of a FeS2 / rGO composite material.

[0012] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0013] A FeS2 / rGO composite material comprises an rGO carrier and FeS2 particles, wherein the FeS2 particles are dispersed on the surface and in the folds of the rGO carrier, and the particle size of the FeS2 particles is 1 to 5 μm.

[0014] The present invention provides a FeS2 / rGO composite material, which can be used to treat VOCs waste gas by using the sulfate radical activation catalysis (SAOPs) technology in the liquid phase advanced oxidation technology. After the composite material of the present invention is in contact with persulfate, SO4 can be generated efficiently and quickly. ·- and · OH and other free radicals with super oxidizing ability, thereby achieving efficient and deep degradation of VOCs waste gas. During the degradation process, VOCs can be decomposed into CO2 and H2O.

[0015] The FeS2 / rGO composite material of the present invention has FeS2 particles, wherein the sulfur sites can act as electron donors to promote iron circulation. 3+ / Fe 2+ The electrode potential (0.77 V) is higher than that of S 2- / S 0 The electrode potential (0.65V) and S 2- It has a lower valence state. Therefore, the addition of S element can meet the conditions for establishing an internal electron circulation system in the catalyst, provide electrons for the reduction process of Fe(III) to Fe(II), and realize the regeneration of catalytic sites.

[0016] Graphene has a high specific surface area and excellent electrical conductivity, making it an ideal carrier for the synthesis of supported transition metal catalysts. The huge surface structure of graphene can not only serve as a growth site for metals, significantly improving the dispersion and exposure of metal catalytic sites, but also use the excellent electrical conductivity of graphene to accelerate the electron transfer rate during the catalytic process and improve the catalytic performance of the catalyst. The regulated graphene carrier can also play a certain adsorption role on VOCs. On the surface of the catalyst, the adsorption of VOCs molecules and the efficient coupling of catalytic oxidation are achieved, ultimately achieving the effect of efficient degradation of VOCs.

[0017] The composite material of the invention has FeS2 particles with a size of 1 to 5 μm. The smaller particle size can avoid the agglomeration of FeS2 and significantly increase the exposed surface of the metal catalytic site.

[0018] Therefore, the composite material of the present invention can solve the problem of difficult regeneration of Fe(II), and does not require excessive oxidant to reduce Fe(III) to achieve regeneration of Fe(II) to generate sufficient strong oxidizing free radicals to ensure effective degradation of target pollutants, and does not cause ineffective consumption of oxidants.

[0019] Preferably, the rGO carrier is obtained by sequentially subjecting GO to ultrasonic treatment and reduction reaction, and the frequency of the ultrasonic wave is 10 to 30 kHz.

[0020] In the FeS2 / rGO composite material of the present invention, GO is treated with ultrasound, which can, on the one hand, break the van der Waals force between graphene layers and peel the graphene into a single-layer structure; on the other hand, the cavitation effect of ultrasound can be used to continuously impact the sheet structure of graphene oxide, causing it to bend and curl inward, generating a large number of internal wrinkles and cavities, thereby anchoring the growth site of the metal and constructing rich organic waste gas (VOCs) adsorption sites.

[0021] By regulating parameters such as the power and frequency of ultrasound, graphene oxide can be oriented to form a 3D rolled structure full of wrinkles and cavities, making it an excellent catalyst carrier and VOCs adsorption material.

[0022] More preferably, the frequency of the ultrasonic wave is 15 to 25 kHz.

[0023] The working conditions of ultrasonic treatment of GO need to be precisely controlled. If the frequency is too low or the power is too small, it will affect the degree of graphene exfoliation and the directional modification of the morphology; if the frequency is too high or the power is too large, the cavity structure of graphene will be too large, resulting in uneven distribution of metal growth during the preparation process.

[0024] In a specific embodiment, preferably, the power of the ultrasound is 200-400w, and the frequency is 10-30kHz, more preferably, the power is 300w, and the frequency is 20kHz.

[0025] The present invention also protects a method for preparing the FeS2 / rGO composite material, comprising the following steps:

[0026] S1. treating graphene oxide in an ultrasonic environment to obtain a graphene oxide turbid solution;

[0027] S2. mixing an organic acid and / or an organic acid salt with the graphene oxide turbid solution of S1;

[0028] S3. Mixing the acidic iron salt solution and the organic sulfur solution with the solution of S2, and hydrothermally reacting at 120 to 200° C. to obtain a FeS2 / rGO composite material;

[0029] Wherein, in step S1, the frequency of the ultrasonic wave is 10 to 30 kHz.

[0030] In the preparation process of the FeS2 / rGO composite material of the present invention, the two-dimensional planar structure of GO is first modified by ultrasound, and it is directionally transformed into a 3D scroll structure full of wrinkles and cavities; then, the modified GO is used as a carrier, and ferrous ions are anchored on the GO substrate by electrostatic adsorption, and FeS2 metal catalyst is in situ grown on the carrier sites rich in GO by hydrothermal method. In the hydrothermal process, GO is reduced to reduced graphene oxide (rGO), so that the carrier has stronger thermal stability, conductivity and hydrophilicity. The whole preparation process is simple, efficient and condition-controllable.

[0031] Before performing step S3, step S2 needs to be performed first because the organic acid and / or organic acid salt in step S2 acts as a metal ion stabilizer and antioxidant.

[0032] In step S3, due to the presence of a large number of internal wrinkles and cavities in GO after ultrasonic treatment, the oxygen-containing functional groups on the inner wrinkle walls have a higher density and stronger electrostatic potential energy, and Fe 2+ It is more inclined to enter the inner fold walls and cavities of GO and become the anchoring point of metal ions through electrostatic adsorption.

[0033] The preparation method of the FeS2 / rGO composite material of the present invention synthesizes a porous catalytic material (FeS2 / rGO) with a 3D scroll structure by in-situ growing FeS2 on a graphene oxide substrate after ultrasonic modification. The modification and steric effect of rGO effectively inhibit the excessive growth and agglomeration of FeS2, significantly improving the exposed surface and catalytic performance of the metal catalytic active sites; the internal wrinkles and cavities of rGO anchor the structure of the FeS2 / rGO catalyst and avoid the loss of metal; the excellent electrical conductivity of rGO accelerates the electron transfer rate in the catalytic process, improves the catalytic efficiency and Fe 3+ To Fe 2+ The cyclic conversion rate significantly improves the performance stability of metal catalysts and avoids the deactivation of catalytic performance. In addition, the 3D rolled porous structure of the material can also serve as an efficient adsorption site for VOCs. VOCs molecules and free radicals with strong oxidizing ability are confined in the narrow micro-nano space of the material, and the migration distance is greatly shortened, making the adsorption and catalytic oxidation process of VOCs highly efficient and coordinated, thereby achieving efficient and deep degradation of VOCs.

[0034] In step S3, the pH value of the iron salt solution is kept at about 5 to avoid Fe 2+ Hydrolysis precipitation occurs.

[0035] The iron salt solution and the organic sulfur solution in step S3 can be the iron source and sulfur source commonly used in the art, which are used for the in-situ growth synthesis of FeS2.

[0036] Preferably, in step S3, the atomic molar ratio of sulfur to iron is (2-8):1.

[0037] When the S:Fe ratio is too low, Fe cannot be effectively fixed by S, and the generated FeS2 is relatively small, resulting in weak catalytic activity; but when the S:Fe ratio is too high, excess S will not only cause a waste of the S element, but also form other crystal forms of iron sulfide, which will change the structure of the material and shield the active sites of FeS2.

[0038] Preferably, in step S3, the hydrothermal reaction time is 8 to 24 hours.

[0039] More preferably, in step S3, the hydrothermal reaction time is 16 to 24 hours.

[0040] The hydrothermal process is accompanied by rising temperature. When the temperature rises, the pressure of the system also gradually increases. The change in pressure can control the size and morphology of the material. Therefore, extending the hydrothermal time so that the precursor is under high pressure for a long time is conducive to the formation of FeS2 with smaller particle size, avoiding the aggregation of FeS2 on the carrier rGO and increasing the dispersion of active sites, thereby obtaining FeS2 / rGO composite materials with better performance.

[0041] Preferably, the organic sulfur is one or more of thioacetamide, thiourea or sodium sulfide.

[0042] More preferably, the organic sulfur is thioacetamide.

[0043] Preferably, the organic acid is one or more of citric acid and malic acid, and the organic acid salt is one or more of sodium citrate and calcium citrate.

[0044] More preferably, the organic acid salt is sodium citrate.

[0045] On the one hand, the three carboxylic acid groups (COO - ) can react with the ferrous ion (Fe 2+ ) combine to form a six-membered ring coordination form, making Fe 2+ The ions are stabilized and are not easily hydrolyzed and precipitated; on the other hand, sodium citrate has strong reducing properties and can be used as an excellent antioxidant to avoid the active Fe 2+ Oxidized to Fe 3+ .

[0046] In a specific embodiment, the preparation method of the FeS2 / rGO composite material may include the following steps:

[0047] S1. Add graphene oxide powder (GO) to water, stir evenly, and then place it in an ultrasonic environment for 30 to 60 minutes;

[0048] S2. Add sodium citrate powder to the graphene oxide turbid solution of S1 and stir evenly until the sodium citrate is completely dissolved;

[0049] S3. Use a peristaltic pump to slowly add the acidic iron salt solution and the organic sulfur solution dropwise into the S2 solution, stirring while adding; then transfer to a stainless steel high-pressure reactor lined with polytetrafluoroethylene, and perform a hydrothermal reaction at 120-200°C for 8-24 hours; after the reaction is completed, cool to room temperature, filter the mixed solution, wash the obtained black precipitate, and vacuum dry to obtain a FeS2 / rGO composite material.

[0050] The method of slowly adding drop by drop using a peristaltic pump is to evenly disperse the iron source and the sulfur source on the sites of graphene oxide to avoid the formation of large metal crystal nuclei.

[0051] In the preparation method of the present invention, the concentrations of graphene oxide, iron ions and organic sulfur will directly affect the contact and kinetic growth of the raw materials. If the concentration is too high, it will lead to too fast crystallization, larger grains, and reduced exposure of metal catalytic sites, resulting in lower reaction activity; if the concentration is too low, the metal crystals will grow slowly, affecting efficiency.

[0052] In a specific embodiment, the graphene oxide powder in S1 is industrial-grade graphene oxide with a purity of 99%. Preferably, the concentration of the graphene oxide solution is 15-30 g / L, more preferably, 20 g / L.

[0053] In a specific embodiment, preferably, the amount of sodium citrate added in S2 is 10-30 g / L, more preferably, 20 g / L.

[0054] In a specific embodiment, preferably, the iron salt of the iron salt solution in S3 is one or more of ferrous chloride, ferrous sulfate, and ferrous nitrate, the concentration of the added ferrous ions is 3-8 g / L, and the dripping rate is 10-30 μL / min. More preferably, the iron salt is ferrous chloride, the concentration of the added ferrous ions is 5 g / L, and the dripping rate is 20 μL / min.

[0055] In a specific embodiment, preferably, the organic sulfur in the organic sulfur solution in S4 is one or more of thiourea, thioacetamide, and sodium sulfide, the concentration of added sulfur atoms is 5-20 g / L, and the drop rate is 10-30 μL / min. More preferably, the organic sulfur is thioacetamide, the concentration of added sulfur atoms is 10 g / L, and the drop rate is 20 μL / min.

[0056] The present invention also protects the use of the above-mentioned FeS2 / rGO composite material in the degradation of continuous flow VOCs waste gas by SAOPs combined with liquid phase absorption method.

[0057] In a specific implementation, the flow rate of the continuous flow VOCs waste gas is 0.2 to 1 L / min, the type of the continuous flow VOCs waste gas is one or more of toluene, chlorobenzene and styrene, and the concentration of the VOCs waste gas is 30 to 100 ppmv.

[0058] The present invention also provides a method for degrading benzene-based VOCs, wherein the benzene-based VOCs are reacted in a persulfate reaction solution containing the above-mentioned FeS2 / rGO composite material.

[0059] In a specific embodiment, the addition amount of the oxidant persulfate is 2-6 g / L, and the addition amount of the FeS2 / rGO composite catalyst is 50-300 mg / L.

[0060] The composite material catalyst of the present invention does not require an additional regeneration method, but only requires the addition of persulfate, and can continuously degrade organic waste gas.

[0061] Preferably, the benzene-based VOCs are one or more of toluene, chlorobenzene or styrene.

[0062] The FeS2 / rGO composite material of the present invention has good universality in degrading VOCs waste gas, and is particularly suitable for degrading toluene, chlorobenzene or styrene, and can be applied to the degradation of actual industrial organic waste gas.

[0063] Compared with the prior art, the present invention has the following beneficial effects:

[0064] The present invention discloses a FeS2 / rGO composite material, comprising an rGO carrier and FeS2 particles, wherein the FeS2 particles are dispersed on the surface and in the folds of the rGO carrier, and the particle size of the FeS2 particles is 1 to 5 μm. The composite material of the present invention can solve the problem of difficulty in regenerating Fe(II), and does not require excessive oxidant to reduce Fe(III) to achieve regeneration of Fe(II) to generate sufficient strong oxidizing free radicals to ensure effective degradation of target pollutants, and does not require ineffective consumption of oxidant.

[0065] The FeS2 / rGO composite material of the present invention can be used to treat VOCs waste gas by using the sulfate radical activation catalysis (SAOPs) technology in the liquid phase advanced oxidation technology. After the composite material of the present invention comes into contact with persulfate, SO4 can be generated efficiently and quickly. ·- and · OH and other free radicals with super oxidizing ability, thereby achieving efficient and deep degradation of VOCs waste gas. During the degradation process, VOCs can be decomposed into CO2 and H2O. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 The X-ray diffraction (XRD) diagrams of the materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown.

[0067] Figure 2 The electrochemical test curves of the materials prepared in Example 1 and Comparative Example 1 are shown.

[0068] Figure 3 These are scanning electron microscope (SEM) images of the materials prepared in Example 1 and Comparative Example 2.

[0069] Figure 4 This is a performance test chart of the FeS2 / rGO composite material in Example 1 for degrading different VOCs.

[0070] Figure 5 This is a test diagram of the cyclic stability performance of the FeS2 / rGO composite material in Example 1 in degrading gaseous toluene. DETAILED DESCRIPTION

[0071] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0072] Graphene oxide, manufacturer is Xianfeng Nano, brand: 7440-44-0.

[0073] Example 1

[0074] A method for preparing a FeS2 / rGO composite material comprises the following steps:

[0075] S1. Add 1 g of graphene oxide powder to 50 mL of water, stir evenly, and place it in an ultrasonic environment with a frequency of 20 kHz for 60 min;

[0076] S2. Take 0.1 g of sodium citrate powder and add it to the graphene oxide turbid solution of S1, and stir evenly until the sodium citrate is completely dissolved;

[0077] S3. Prepare an acidic iron salt solution: dissolve 0.88 g of ferrous chloride (FeCl2·4H2O) in 5 mL of water, and add dilute hydrochloric acid to adjust the pH to 5; slowly add the iron salt solution dropwise to the solution of S2 at a rate of 20 μL / min using a peristaltic pump, stirring while adding;

[0078] Prepare the organic sulfur solution: dissolve 1.35 g of thioacetamide (C2H5NS) in 5 mL of water; slowly add the organic sulfur solution dropwise into the above solution at a rate of 20 μL / min using a peristaltic pump, stirring while adding dropwise;

[0079] The mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and subjected to hydrothermal reaction at 160 °C for 24 h;

[0080] After the reaction was completed, the mixture was cooled to room temperature, the mixed solution was filtered, the obtained black precipitate was washed, and it was vacuum dried at 60° C. for 10 h to obtain a FeS2 / rGO composite material.

[0081] Among them, the atomic molar ratio of sulfur to iron in S3 is S:Fe=4:1.

[0082] Example 2

[0083] A FeS2 / rGO composite material comprises the same steps as those in Example 1, except that the atomic molar ratio of sulfur to iron in S3 is S:Fe=2:1.

[0084] Example 3

[0085] A FeS2 / rGO composite material comprises the same steps as those in Example 1, except that the atomic molar ratio of sulfur to iron in S3 is S:Fe=6:1.

[0086] Example 4

[0087] A FeS2 / rGO composite material comprises the same steps as those in Example 1, except that the atomic molar ratio of sulfur to iron in S3 is S:Fe=8:1.

[0088] Example 5

[0089] A FeS2 / rGO composite material comprises the same steps as those in Example 1, except that the hydrothermal reaction time in S3 is 8 hours.

[0090] Example 6

[0091] A FeS2 / rGO composite material comprises the same steps as those in Example 1, except that the hydrothermal reaction time in S3 is 16 hours.

[0092] Example 7

[0093] A method for preparing a FeS2 / rGO composite material comprises steps substantially the same as those of Example 1, except that the type of organic sulfur in S3 is thiourea (CH4N2S).

[0094] Example 8

[0095] A method for preparing a FeS2 / rGO composite material comprises steps substantially the same as those of Example 1, except that the type of organic sulfur in S3 is sodium sulfide (Na2S).

[0096] Example 9

[0097] A method for preparing a FeS2 / rGO composite material comprises steps substantially the same as those in Example 1, except that in S1., the ultrasonic frequency is 10 kHz.

[0098] Example 10

[0099] A method for preparing a FeS2 / rGO composite material comprises steps substantially the same as those in Example 1, except that in S1., the ultrasonic frequency is 30 kHz.

[0100] Comparative Example 1

[0101] An iron sulfide catalyst (FeS x ), comprising the following steps:

[0102] S1. Add 0.1 g of sodium citrate powder to 50 mL of water and stir until the sodium citrate is completely dissolved;

[0103] S2. Prepare an acidic iron salt solution: dissolve 0.88 g of ferrous chloride (FeCl2·4H2O) in 5 mL of water, and add dilute hydrochloric acid to adjust the pH to 5; slowly add the iron salt solution dropwise to the solution of S1 at a rate of 20 μL / min using a peristaltic pump, stirring while adding;

[0104] S3. Prepare an organic sulfur solution: dissolve 1.35 g of thioacetamide (C2H5NS) in 5 mL of water; slowly add the organic sulfur solution dropwise to the solution of S2 at a rate of 20 μL / min using a peristaltic pump while stirring;

[0105] S4. The mixed solution of S3 was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and subjected to a hydrothermal reaction at 160°C for 24 h;

[0106] S5. After the reaction is completed, the mixture is cooled to room temperature, the S5 mixture is filtered, the black precipitate obtained by washing is dried under vacuum at 60°C for 10 h to obtain FeS x catalyst.

[0107] The difference from Example 1 is that no rGO carrier is included.

[0108] Comparative Example 2

[0109] A method for preparing an rGO carrier comprises the following steps:

[0110] S1. Add graphene oxide powder to water, stir evenly, and place it in an ultrasonic environment with a frequency of 20 kHz for 60 minutes;

[0111] S2. The mixed solution of S1 was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and subjected to a hydrothermal reaction at 160°C for 24h;

[0112] S3. After the reaction is completed, cool to room temperature, filter the S3 mixed solution, wash the obtained black precipitate, and dry it in vacuum at 60°C for 10 hours to obtain the rGO carrier.

[0113] The difference from Example 1 is that no FeS2 particles are included.

[0114] Results

[0115] (1) XRD test: Figure 1 The X-ray diffraction (XRD) diagrams of the composite material of Example 1 and the rGO carrier of Comparative Example 2 are shown in FIG. Figure 1It can be seen that the XRD spectrum of the rGO carrier prepared in Comparative Example 2 shows the (0 0 2) crystal plane of reduced graphene oxide (rGO) at 2θ=24.5°, indicating that the raw material GO has been completely converted into reduced graphene oxide rGO after hydrothermal reduction. The XRD spectrum of the FeS2 / rGO composite material prepared in Example 1 shows sharp metallic characteristic diffraction peaks at 2θ=24.5°, 32.94°, 36.92°, 40.62°, 47.32° and 56.08°, corresponding to the (2 0 0), (2 10), (2 2 1), (2 2 0) and (3 1 1) crystal planes of pyrite (FeS2), indicating that the method has successfully synthesized a composite material with FeS2 / rGO as the main component. The XRD spectrum of the iron sulfide catalyst prepared in Comparative Example 1 also shows the presence of pyrrhotite (Fe 1-x The characteristic diffraction peaks of pyrite (FeS2) and marcasite (FeS2) indicate that in the absence of rGO carrier, metal aggregates grow and the formed catalyst has more impurities and poor purity.

[0116] (2) Electrochemical test: The composite material of Example 1 and the iron sulfide catalyst (FeS x ) Electrochemical test was performed by electrochemical workstation. The test results are as follows Figure 2 As shown. Figure 2 As shown in (a), it can be found that the CV curve of FeS2 / rGO has a larger loop area and current density, indicating that FeS2 / rGO has better conductivity. Figure 2 As shown in (b), FeS x In comparison, FeS2 / rGO also presents a smaller semicircle in the high-frequency region of the Nyquist diagram, which further indicates that the addition of rGO effectively improves the electron transport capacity of the catalyst and significantly enhances the catalytic performance.

[0117] (3) SEM and EDS testing: Use SEM and EDS to observe the morphological characteristics and element distribution of the material.

[0118] Figure 3 (b) is a scanning electron microscope image of the rGO carrier prepared in Comparative Example 2. In order to observe the effect of ultrasonic frequency on the morphology of reduced graphene oxide (rGO) in Examples 8 and 9, the graphene oxide (GO) was treated by the same method as in Comparative Example 2, except that the ultrasonic frequencies were 10 kHz and 30 kHz, respectively. The test results are shown in Table 1. Figure 3 (a) and Figure 3 (c). Figure 3(ac) In comparative example 2, the ultrasonic frequency is 20kHz, forming a 3D scroll structure with a huge specific surface area and wrinkled cavities, which can provide a good growth space for FeS2 particles and can be used as an ideal carrier for metal catalysts. When the ultrasonic frequency is low, such as Figure 3 As shown in (a), the obtained rGO carrier layers have not been completely peeled off, there is an obvious stacking phenomenon, and there are relatively few cavity structures, which has a certain negative impact on the loading growth of the metal. When the ultrasonic frequency is too high, such as Figure 3 As shown in (c), the ultrasonic cavitation effect is more obvious, and the cavity volume of the rGO carrier is further increased. The excessively large cavity has a certain negative impact on the uniform distribution of the metal catalyst.

[0119] like Figure 3 As shown in (d), FeS prepared in Comparative Example 1 x When the catalyst lacks the constraint of the carrier rGO, the particle size of the formed particles is 10-25μm, and there is obvious agglomeration between the metal particles, which is not conducive to the exposure of catalytic active sites.

[0120] like Figure 3 (ef) shows the FeS2 / rGO composite material prepared in Example 1, in which FeS2 grows in a spherical form and is randomly dispersed on the surface and folds of rGO. Due to the steric effect of rGO, the dispersion of metal sites is greatly increased, avoiding the agglomeration of FeS2. The particle size is 1-5 μm, which significantly increases the exposure surface of the metal catalytic sites.

[0121] Figure 3 (g) is the C, Fe, and S element mapping diagram of the FeS2 / rGO composite material, which confirms that Fe and S are uniformly dispersed on the rGO substrate, indicating that FeS2 is successfully loaded on the surface and wrinkles of rGO.

[0122] (4) Degradation of continuous flow VOCs waste gas test:

[0123] Specific test method: S1. Put the FeS2 / rGO composite material prepared in each example into the reaction liquid (pure water) of the wet AOP scrubber, stir it to make it dispersed evenly, and control the mass concentration of the catalyst to be 0.3g / L; S2. Add potassium persulfate (PMS, CAS No. 70693-62-8) to the above reaction liquid, and control the mass concentration of PMS to be 2g / L. At this time, the catalyst will quickly generate a large number of highly active free radicals such as HO after contacting with PMS. · 、SO4 ·- 、O2 ·- and 1O2, etc. S3. The VOCs waste gas is passed through the gas diffusion device and introduced into the reaction liquid from the bottom of the reactor for degradation reaction. The concentration of the VOCs waste gas is controlled to be 30ppmv, and the ratio of the flow rate of the VOCs waste gas per unit time (min) to the volume of the reaction liquid is controlled to be 1:1.

[0124] It should be noted that after VOCs gas enters from the bottom of the liquid, it is rapidly enriched and captured by the adsorption sites of the catalyst. At the same time, the highly active free radicals generated on the catalyst attack and destroy the molecular structure of VOCs through electrophilic addition and electron transfer, and gradually oxidize them into non-toxic CO2 and H2O, ultimately achieving efficient and deep degradation of VOCs.

[0125] Toluene removal rate (%) = (inlet concentration of toluene - outlet concentration of toluene) / inlet concentration of toluene * 100%.

[0126] The outlet CO2 concentration reflects the amount of CO2 produced after toluene is oxidized and degraded. The higher the value, the more thorough the degradation of toluene; the lower the value, the more liquid intermediates are produced after toluene degradation.

[0127] The following test data is for a reaction time of 60 minutes.

[0128] The test results are shown in Table 1:

[0129] Table 1

[0130]

[0131]

[0132] It can be seen from the above results that the FeS2 / rGO composite material of the embodiment of the present invention can use the sulfate radical activation catalysis (SAOPs) technology in the liquid phase advanced oxidation technology to treat VOCs waste gas. After the composite material of the present invention comes into contact with persulfate, SO4 can be generated efficiently and quickly. ·- and · OH and other free radicals with super strong oxidizing ability, thereby achieving efficient and deep degradation of VOCs waste gas, and VOCs can be decomposed into CO2 and H2O during the degradation process. When the composite material of the present invention degrades toluene, the toluene removal rate can reach more than 63%, up to 94%, and the outlet CO2 concentration can reach more than 27ppmv, up to 81ppmv.

[0133] It can be seen from Examples 1 to 4 that when the sulfur-iron ratio (S:Fe) is (4 to 8):1, it is more conducive to improving the removal rate of toluene. This is because the S:Fe ratio needs to be adjusted to a suitable ratio to obtain a crystalline structure that is conducive to activating PMS and achieving the purpose of efficiently and stably degrading VOCs.

[0134] It can be seen from Examples 1 and 5 to 6 that the hydrothermal reaction time is higher and the prepared FeS2 / rGO has higher catalytic activity and mineralization effect.

[0135] It can be seen from Examples 1 and 9 to 10 that the toluene removal rate in Example 1 is higher, indicating that the ultrasonic frequency of 15 to 25 kHz is more conducive to reducing graphene oxide to form a 3D rolled structure with a large specific surface area and wrinkled cavities, providing a more excellent growth space for FeS2 particles.

[0136] In order to verify the universality of FeS2 / rGO catalyst, the pollutant types were expanded from toluene to chlorobenzene and styrene. The test results are as follows Figure 4 As shown. Figure 4 It can be seen that the FeS2 / rGO catalyst prepared in Example 1 shows excellent degradation effect on aromatic hydrocarbon VOCs in the atmosphere. The degradation rates of toluene, styrene and chlorobenzene are 94%, 96% and 88%, respectively, and the outlet CO2 concentrations are 81ppmv, 92ppmv and 71ppmv, respectively, indicating that the FeS2 / rGO composite material has good universality in degrading VOCs waste gas and can be used for the degradation of actual industrial organic waste gas.

[0137] It can be seen from the embodiment and comparative example 2 that the rGO carrier of comparative example 2 also has a certain removal rate for toluene, indicating that the carrier rGO has abundant adsorption sites and can effectively adsorb VOCs gas. The removal rate of toluene by the composite material of the embodiment of the present invention is significantly higher than that of comparative example 2, indicating that the FeS2 / rGO composite catalyst of the present invention has abundant adsorption sites and catalytic sites at the same time, and realizes efficient coupling of adsorption and catalytic oxidation in the process of degrading VOCs gas, and finally achieves the effect of efficient degradation of VOCs.

[0138] The cyclic stability performance test of the FeS2 / rGO composite material in Example 1 for degrading gaseous toluene is shown in the following results: Figure 5 As shown, the inventors found that as the reaction proceeded, the toluene removal efficiency would show a downward trend. When the downward trend appeared, persulfate was immediately added and the efficiency was found to be immediately restored. This was achieved by repeating 6 times, proving that the catalyst performance was stable.

[0139] from Figure 5 It can be seen that after a long-term performance test of 360 minutes, the FeS2 / rGO catalyst still maintains a degradation rate of more than 90% for toluene, proving that the composite catalyst of the present invention has good stability.

[0140] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A FeS2 / rGO composite material, characterized in that: The invention comprises an rGO carrier and FeS2 particles, wherein the FeS2 particles are dispersed on the surface and in the folds of the rGO carrier, and the particle size of the FeS2 particles is 1 to 5 μm.

2. The FeS2 / rGO composite material according to claim 1, characterized in that The rGO carrier is obtained by sequentially subjecting GO to ultrasonic treatment and reduction reaction, and the frequency of the ultrasonic wave is 10 to 30 kHz.

3. The method for preparing the FeS2 / rGO composite material according to claim 1 or 2, characterized in that: The steps include: S1. treating graphene oxide in an ultrasonic environment to obtain a graphene oxide turbid solution; S2. mixing an organic acid and / or an organic acid salt with the graphene oxide turbid solution of S1; S3. Mixing the acidic iron salt solution and the organic sulfur solution with the solution of S2, and hydrothermally reacting at 120 to 200° C. to obtain a FeS2 / rGO composite material; Wherein, in step S1, the frequency of the ultrasonic wave is 10 to 30 kHz.

4. The method for preparing the FeS2 / rGO composite material according to claim 3, characterized in that: In step S3, the atomic molar ratio of sulfur to iron is (2-8):

1.

5. The method for preparing the FeS2 / rGO composite material according to claim 3, characterized in that: In step S3, the hydrothermal reaction time is 8 to 24 hours.

6. The method for preparing the FeS2 / rGO composite material according to claim 3, characterized in that: The organic sulfur is one or more of thioacetamide, thiourea or sodium sulfide.

7. The method for preparing the FeS2 / rGO composite material according to claim 3, characterized in that: The organic acid is one or more of citric acid and malic acid, and the organic acid salt is one or more of sodium citrate and calcium citrate.

8. Use of the FeS2 / rGO composite material according to claim 1 or 2 in the degradation of continuous flow VOCs waste gas by SAOPs combined with liquid phase absorption method.

9. A method for degrading benzene-based VOCs, characterized in that: The benzene-based VOCs are reacted in a persulfate reaction solution containing the FeS2 / rGO composite material described in 1 or 2.

10. The degradation method according to claim 9, characterized in that: The benzene-based VOCs are one or more of toluene, chlorobenzene or styrene.

Citation Information

Patent Citations

  • Ferrous activation persulfate slow-release candle for underground water in-situ oxidation restoration

    CN106477709A

  • Method for regulating and controlling FeS2 / reduced graphene oxide compact assembly structure

    CN112062165A

  • Electro-Fenton catalyst and preparation method and application thereof

    CN112295573A

  • MnFe2O4 / rGO nano electrode material with ultra-small particle size as well as preparation method and application of MnFe2O4 / rGO nano electrode material

    CN118026366A